Variación temporal de la concentración de bacterias heterotróficas, vibrios y pseudomonas durante la transición intermareal en el estero Huayla - Bustamante Carrion, Karen Cecibel; Lopez Olives, Paul Arsenio (Machala : Universidad Técnica de Machala, 2024)
Vibrios and Pseudomonas are common pathogenic microorganisms in marine water bodies and are a natural part of the environment. The amount of these microorganisms can vary depending on the type of tide and the lunar phase in which it is found. The present work was carried out to analyze the temporal variation of the concentration of Vibrios and Pseudomonas during the intertidal transition in the Estero Huaylá, using microbiological cultures to determine the differences in the concentration of bacteria in the two intertidal states. TCBS agar was used for the identification of Vibrios and Cetrimide agar for the identification of Pseudomonas, with dilutions of 10-1/10-2. With the results obtained, it was determined that during low tide the greatest number of Vibrioss and Pseudomonas microorganisms existed. The ANOVA test with Duncan's test (p<0.05) determined that the Vibrioss load in the Waning Moon phase was 942.50 CFU/ml, significantly different from the concentrations of the other lunar phases. However, the results obtained in this study indicate that during the Full Moon, a higher concentration of Vibrios (762.11 CFU) was observed compared to the other lunar phases. Finally, the New Moon presented the highest concentration of Pseudomonas, with values of 3272 CFU.
Los Vibrios y Pseudomonas son microorganismos patógenos comunes en cuerpos de agua marina, formando parte natural del medio. La cantidad de estos microorganismos puede variar según el tipo de marea y la fase lunar en la que se encuentre. El presente trabajo se realizó con el objetivo de analizar la variación temporal de la concentración de Vibrios y Pseudomonas durante la transición intermareal en el Estero Huaylá, mediante cultivos microbiológicos para determinar las diferencias en la concentración de bacterias en los dos estados intermareales. Se utilizo el agar TCBS para identificar Vibrios y el agar Cetrimide para la identificación de Pseudomonas, con diluciones de 10-1/10-2. Con los resultados obtenidos se determinó que en bajamar existió la mayor cantidad de microorganismos Vibrios y Pseudomonas. La prueba de ANOVA con test de Duncan (p <0,05), se determinó que la carga de Vibrios en la fase Luna Menguante fue de 942,50 UFC/ml significativamente diferente a las concentraciones de las otras fases lunares. Sin embargo, los resultados obtenidos en este estudio indican que durante la Luna Llena se observó una mayor concentración de Vibrios (762,11 UFC/ml) en comparación con las otras fases lunares. Finalmente, la Luna Nueva presentó la concentración más alta de Pseudomonas, con valores de 3272 UFC/ml.
Keywords: VIBRIOS; PSEUDOMONAS; VARIACION INTERMAREAL; CICLO LUNAR